Public-Private Partnership: Pathway to Educational Development in Nigeria - Adeagbo, Joseph O (Archives of Business Research, 2023)
This paper has provided evidence on the impact of public and private partnership on educational development in Nigeria, using OLS methodology in analysing the time series data from 1980-2020 best linear unbiased estimator (BLUE). The study found that government allocation to education in Nigeria fall below18% for past decades. However this can be augmented by private sector contribution to education which is derived as the proportionate of total expenditure on education and this form the basis for modelling the impact of public and private partnership on educational development. It was found that the estimated value of R2 (goodness of fit) of 0.98 or 98% shows that 98% systematic variation in Educational Productivity is caused by variation in total labour force, unemployment rate, inflation rate, public expenditure on education, private expenditure on education and gross fixed capital formation. The study conclude that public participation in financing education is not enough for effective funding of education but private sector can also argument the expenses in order to produce skilful and economic active labour force. Recommendation was made that there is need to increase budgetary allocation to the educational sector and also create an enabling environment for development of private sector which will improve educational productivity either by funding it or by employment.